The Efficiency of Nitrogen Compounds Removal in Wastewater Treatment Plant = Ocena efektywności pracy oczyszczalni ścieków o RLM 45000 - Suchowska-Kisielewicz, Monika; Sieciechowicz, Aleksandra; Sadecka, Zofia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In sewage treatment plants for removing nitrogen compounds are used biological processes of nitrification and denitrification. The parameters determining the efficiency of biological processes of nitrogen removal are organic carbon ratio (BOD5) to total Kjeldahl nitrogen (TKN), temperature and pH. The impact of these parameters on the operation of the sewage treatment plant with an RLM of 45,000 based on operational data from the period 2011-2013 has been assessed.
Keywords: nitrogen removal; BOD5/TKN ratio; wastewater temperature; usuwanie związków azotu; temperatura ścieków